Implementasi YOLOv8 Dalam Penghitung Masuk dan Keluar Manusia Pada Gedung - Fahrezi, Muhammad Azril; Widiyanto, Eka Puji (JATISI, 2024)
The rapid development of technology has made various human activities more efficient and easier to carry out. One of the innovations commonly used in communication technology is surveillance cameras. Surveillance cameras can be utilized as security monitoring tools, such as counting the number of people entering and exiting a building. Counting the number of people entering and exiting is a method often used as a security measure or for evaluating business premises. However, many buildings or businesses still manually count the number of people entering and exiting, which can lead to errors in the counting process. The aim of this research is to develop an application that can automatically count the number of people entering and exiting a building using a camera. The method used is You Only Look Once Version 8 (YOLOv8). YOLOv8 is a fast and accurate object detection model. The implementation results showed a precision of 79.6%, a recall of 61.7%, and a mean average precision (mAP) of 72.3%.